Pengaruh Persepsi Penggunaan dan Persepsi Risiko Terhadap Minat Menggunakan Dompet Digital Melalui Aplikasi Shopeepay Sebagai Alat Pembayaran Non-Tunai Pada Generasi Z (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
The rapid growth of financial technology has led to the emergence of digital wallets as an efficient and practical means of payment. One of the most widely used services in Indonesia is Shopeepay, particularly among Generation z, who are known for their adaptability to new technologies. This study aims to examine the influence of perceived usefulness (X1) and perceived risk (X2) on the intention to use digital wallets (Y), with Shopeepay payment method (M) as a moderating variable. This research employed a quantitative approach by distributing questionnaires to 60 University students who actively use Shopeepay. The collected data were analyzed using multiple linier regression and Moderated Regression Analysis (MRA). The findings reveal that perceived usefulness has a positive and significant effect on the intention to use Shopeepay. Perceived risk also shows a significant effect in the multiple regression test, but becomes insignificant when tested with MRA. This suggests that impact of risk tends to weaken when moderated by the payment method. Furthermore, the Shopeepay payment method itself does not significantly influence user intention collectively, perceived usefulness and perceived risk significantly affect the intention to use Shopeepay. The findings contribute to understanding digital payment adoption behavior among Generation Z and provide insights for fintech developers to enhance user trust, security, and engagement.